Kelayakan Operasional Hotel Nonbintang di Sulawesi Selatan - Daniel Adolf Ohyver; Nursjam Nursjam; Kurnia Yusniar Rahman (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2020)
This research aims to know the condition of non-star hotels in relation to product, service and management aspects. In addition, this research was also carried out with the intention of evaluating the feasibility of operating non-star hotels in South Sulawesi. This type of research is applied research with a qualitative approach. Information is obtained through observation using check lists, interviews, and documentation in the form of assessment guidelines. Determination of informants was taken in 10 regions with a total of 56 hotels, each hotel has one informant, plus 10 informants from the Regional Tourism Office, so the number of informants became 66 people. The analysis technique used is descriptive analysis. The results showed that, of the 56 non-starred hotels studied there were 23 that were less feasible, 19 were feasible and 14 were very feasible.